The Role of the Pandeglang Regency Inspectorate in Overseeing the Performance of Regional Government Agencies - Ahmad Rifa’i; Ari Supriadi; Alya Rahma (ijd-demos, 2025)
This study aims to analyze the role of the Pandeglang Regency Inspectorate in overseeing the performance of Regional Apparatus Organizations (OPD) and to identify the supporting and inhibiting factors involved in this oversight. The research is grounded in George R. Terry’s (1972) theory of supervision, which encompasses measuring work results, comparing performance against standards, and correcting deviations. A descriptive qualitative approach was employed, utilizing primary data (observations and interviews) and secondary data (documentation and literature reviews). Informants were selected via purposive sampling, and data analysis involved data collection, reduction, presentation, and conclusion drawing. The results indicate that the Pandeglang Regency Inspectorate’s role in overseeing OPD performance focuses on administrative audits but also extends to assessing performance achievements, program implementation effectiveness, budget utilization efficiency, and governmental accountability. The primary supporting factor is the availability of clear regulations and guidelines underpinning the Government Agency Performance Accountability System (SAKIP), while the most dominant inhibiting factor is limited human resources, regarding both quantity and competence. In conclusion, the oversight of Regional Apparatus Organization performance has been effectively carried out in the capacity of the Government Internal Supervisory Apparatus (APIP). Keywords: Inspectorate, Performance Oversight, Regional Apparatus Organization (OPD), Government Internal Supervisory Apparatus (APIP).